A Companion to Latin Greece - Tsougarakis, Nickiphoros I. (Brill's Companions to European History Ser, 2015)
Contents -- List of Figures and Maps -- Notes on Contributors -- Note on Rendition of Proper Names and Transliteration -- Chapter 1 The Latins in Greece: A Brief Introduction -- Chapter 2 Crusades and Crusaders in Medieval Greece -- Chapter 3 Land and Landowners in the Greek Territories under Latin Dominion, 13th-14th Centuries -- Chapter 4 Society, Administration and Identities in Latin Greece -- Chapter 5 The Latin and Greek Churches in former Byzantine Lands under Latin Rule -- Chapter 6 The Economy of Latin Greece -- Chapter 7 Money and Currency in Medieval Greece -- Chapter 8 The Jewish Communities in the Social Fabric of Latin Greece: Between Segregation and Interaction -- Chapter 9 Literature in Frankish Greece -- Chapter 10 The Landscape of Medieval Greece -- Chapter 11 Monumental Art in the Lordship of Athens and Thebes under Frankish and Catalan Rule (1212-1388): Latin and Greek Patronage -- Chronological Table -- Maps -- Collected Bibliography -- Index.